A non-fluorinated superhydrophobic composite coating with excellent anticorrosion and wear-resistant performance - Xiao, Peng; Yang, Liheng; Liu, Jianjun; Zhang, Xiaoqin; Chen, Dabing (Frontiers in Chemistry, 2022)
The facile and low-cost fabrication of fluorine-free superhydrophobic metal surfaces for anti-corrosion remains a challenging issue. Here, we report a superhydrophobic coating based on polyacrylate/SiO2 nano-particles/graphene oxide sheets through simple yet environmentally friendly method. The as-prepared composite coating sprayed on metal surface exhibits excellent superhydrophobic and corrosion-resistant properties. Furthermore, the coating surface possesses good anti-wear performance and remains the superhydrophobicity after harsh abrasion test. Prospectively, the developed non-fluorinated superhydrophobic coating opens up the opportunities for the application in industrial anti-corrosion field.